Theoretical Approaches of Afghan Linguists on the Classification of Compounds and Copulative Compound Words (Texas Journal of Philology, Culture and History, 2023)
This article is devoted to the study of the theoretical opinions of Afghan linguists regarding Pashto compounds and copulative compound words, the purist tendency, the analysis of their opinions on this topic, and the emerging problems, in particular, the problems of classification. Also, the article discusses copulative compound words, copulative phraseological combinations and free copulative phrases.